A Distinctive Growth Cure for a Group of Children with Academic Learning Problems. - Dolan, Anne Brown; Matheny Jr., Adam P. (Journal of Learning Disabilities, 1978)
Examines the physical growth of learning disabled school-aged twin children. Developmental characteristics of children with academic learning problems; Downward deflection in growth parameters of learning disabled children; Relationship of growth deflection to health histories of children; Explanations to the growth curve observed.